PENGGUNAAN TEPUNG MAIZENA, TAPIOKA DAN BERAS SEBAGAI SUMBER KARBON PADA BIOFLOK UNTUK PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Yasin, Muhammad Noor; Maryani, Maryani; Muhlisin, Muhlisin (JURNAL AKUAKULTURA, 2021)
The purpose of this research was to determine the effectiveness of using maizena, tapioca and rice flour as carbon sources in the biofloc system for specific growth rate, survival rate, and feed conversion ratio of nile tilapia. This research used a Completely Randomized Design (CRD), which consisted of three treatments with three replications. Treatment A use maizena flour as carbon source much 2 grams / L of water, treatment B use white rice flour as carbon source much 2 grams / L of water, and treatment C use tapioca flour as carbon source much 2 grams / L of water. Starter bacteria use EM4 much 2 ml / L of water. Maintenance of nile tilapia is carried out for 28 days. The research variables are specific growth rate, survival rate, feed conversion ratio and water quality parameters. The results showed that the use of maizena, tapioca and rice flour as carbon sources in biofloc was not significantly different (P> 0.05) on specific growth rates, survival rate, and feed conversion ratio of nile tilapia (Oreochromis niloticus). The specific growth rates achieved in treatments A, B and C are 2.36; 2.27; and 2.90% / day. The survival rate value reaches 76; 74; and 85%. Value of feed conversion ratio are 1.3; 1.8; and 1.1. The results of measuring water quality in general are in a good range. This research shows that carbon sources using tapioca flour are better than carbon sources using maizena flour and rice flour.